Co-morbidity and cardiovascular risk assessment among Type-2 diabetes mellitus patients: A preliminary study at a public primary care clinic in Kuantan, Malaysia - Tin, Myo Han; Abdullah, Fa’iza; Md Aris, Mohd Aznan; Ismail, Ida Zuriaty (Academy of Family Physicians of Malaysia and Family Medicine Specialist Association, 2015)
Diabetes mellitus (DM) patients with cardiovascular (CVD) co-morbidity have higher risk of mortality. Hypertensions, dyslipidaemia, ischemic heart disease (IHD) are common CVD co-morbidity for DM patients. This study was done to determine relationship among CVD comorbidity, risk assessment and glycemic control status of type-2 DM patients.